The Effect of Good Corporate Governance and Intelectual Capital on Company Value in the LQ45 - Reyna Assyifa Mahawijaya; Ade Imam Muslim (Kajian Akuntansi, 2023)
This study aims to determine the effect of good corporate governance and intellectual capital on company value in the LQ45 index for the 2012-2021 period. The good corporate governance variable uses an independent board of commissioners, intellectual capital uses the Value Added Intellectual Coefficient (VAIC), and firm value uses Tobin's Q. The method used is quantitative. Data were analyzed using the classical assumption test, multiple linear regression analysis, coefficient of determination, partial test (t-test), and simultaneous test (F-test). The results show that good corporate governance and intellectual capital partially and simultaneously have a significant influence on firm value, with an R-Square value of 87.80% while the remaining 12.2% is influenced by other variables not observed in this research.